Efektivitas Program Meditasi Buddhis Terstruktur (Mindful Resilience After Stroke - MRAS) terhadap Regulasi Emosi dan Kualitas Hidup Pasien Pasca Stroke - Ratnasari Ratnasari (Jurnal Budi Pekerti Agama Buddha, 2025)
Impaired emotion regulation and decreased quality of life are common, yet often untreated, sequelae of stroke. Conventional rehabilitation primarily targets physical and cognitive recovery, leaving affective disturbances unaddressed. This study examined the efficacy of a structured Buddhist meditation program—Mindful Resilience After Stroke (MRAS)—for improving emotion regulation and quality of life in stroke survivors. Forty-two ischemic/hemorrhagic stroke patients (3–18 months post-onset) were consecutively recruited and randomly allocated to an intervention group (n = 21) receiving an 8-week MRAS protocol (1 × 60 min/week) or a control group (n = 21) receiving standard care only. Emotion regulation was assessed with the Difficulties in Emotion Regulation Scale-Short Form (DERS-SF) and quality of life with the Stroke-Specific Quality of Life Scale (SS-QOL). Between-group changes (Δ post-pre) were analyzed using independent t-tests or Mann–Whitney U tests (α = 0.05). The intervention group showed a significantly greater reduction in emotion-regulation difficulties than controls (ΔDERS-SF −18.4 ± 5.1 vs. −3.2 ± 4.3; p < 0.001; d = 1.62). Quality-of-life gains were also larger in the intervention group (ΔSS-QOL 35.7 ± 8.9 vs. 7.1 ± 6.5; p < 0.001; d = 1.89). The most improved sub-domains were emotional acceptance, emotional awareness, and impulse control (DERS-SF), as well as energy, mood, and social participation (SS-QOL). No intervention-related adverse events were reported. MRAS is an effective and safe adjunctive intervention to enhance emotion regulation and quality of life after stroke. Embedding mindfulness practices grounded in Buddhist tradition into stroke rehabilitation offers a holistic, culturally adaptable approach for neuropsychological services in Indonesia.